2011
DOI: 10.1510/icvts.2010.255257
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative B-type natriuretic peptide, and not the inflammation status, predicts an adverse outcome for patients undergoing heart surgery☆

Abstract: BNP correlates with clinical endpoints more than inflammatory markers and can be used as a predictor of early outcome after heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…It has been suggested that BNP acts as an important prognostic indicator in the CHF patients, however, NT-proBNP is considered to be a stronger risk bio-indicator for cardiovascular events (Doust et al, 2005). Both BNP and NT-proBNP seem to provide an ideal tool to be utilized as blood tests to diagnose cardiac disorders in patients with high risk of heart failure, diabetes, chronic kidney disease, and coronary artery disease (Khan et al, 2006; Freestone et al, 2008; Czucz et al, 2011; Ganem et al, 2011). The BNP level is increased to almost 200 pg/ml and NT-proBNP levels reaches to approximately 1200 pg/ml in patients with reduced creatinin clearance (McCullough et al, 2003; Anwaruddin et al, 2006).…”
Section: Natriuretic Peptides Synthesis and Secretionmentioning
confidence: 99%
“…It has been suggested that BNP acts as an important prognostic indicator in the CHF patients, however, NT-proBNP is considered to be a stronger risk bio-indicator for cardiovascular events (Doust et al, 2005). Both BNP and NT-proBNP seem to provide an ideal tool to be utilized as blood tests to diagnose cardiac disorders in patients with high risk of heart failure, diabetes, chronic kidney disease, and coronary artery disease (Khan et al, 2006; Freestone et al, 2008; Czucz et al, 2011; Ganem et al, 2011). The BNP level is increased to almost 200 pg/ml and NT-proBNP levels reaches to approximately 1200 pg/ml in patients with reduced creatinin clearance (McCullough et al, 2003; Anwaruddin et al, 2006).…”
Section: Natriuretic Peptides Synthesis and Secretionmentioning
confidence: 99%
“…Interindividual variations in the initial inflammatory response designated as postoperative complication vectors (32)(33)(34)(35)(36), could thus be a risk factor of postoperative infection. To date, no study evidenced clinical or biological factors that could strongly predict postoperative infectious complications (7)(8)(9)37,38). Other studies investigated the relationship between inflammation activation and the occurrence of secondary bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…Events were specifically gated on granulocytes. [Color figure can be viewed at wileyonlinelibrary.com] serious organ failures in the postoperative period, as reflected by a higher SOFA score on D0 (median SOFA: 6 [6][7] vs. 5 [4][5][6], P = 0.037) and on D1 (median SOFA: 2 [1][2][3][4][5] vs. 6 [4][5][6][7][8], P = 0.029). No other preoperative or intraoperative clinical and biological parameters were associated with early postoperative infectious complications ( Supplementary Table S4).…”
Section: Link Between Postoperative Leukocyte Subset and Infectious Cmentioning
confidence: 99%
“…Für Patienten, die sich kardialen Operationen unterziehen müssen, belegt eine aktuelle Arbeit in Analogie zu den nichtkardialen Operationen, dass die B-natriuretischen Peptide besser als die klassischen Entzündungsparameter das Risiko der Patienten abschätzen können [19]. Auch hier fehlen prospektive Studien, die den Einfluss der präoperativen Bestimmung auf die perioperative Mortalität und Letalität aufzeigen.…”
Section: Introductionunclassified